Educriança: vivências educativas de crianças e suas mães - um estudo sobre o olhar das mães no tempo de experiência de um programa de educação da infância - Lima, Eneide Maria Moreira de (2011)
This study is to understand if it is possible to build a new knowledge about popular childhood in the early years of life, in a public education action called Educriança programme, which included mothers, children and educators. The justification for this tidy is the presence and no presence in public schools of children in the early years of life, coming from the poorest families. Through the mothers' point of view, we tried to approach the various meanings that they attribute to the crossings made in the time that they lived with their sons and daughters in this innovative experience of public education, shared with other children and educators of the Program. In this study, we Assume that it is necessary to contextualize the social world in which those women/mothers live, because from their experiences, their crossings, we can understand the different meanings they attach to Educrian,ca Programme. The theoretical basis for this study assumes education as a social practice that does not occur exclusively in the institutions of the education system, especially for children from zero to three years. In this theoretical perspective, the subject departs from the naturalizing views, considering that the human subjective capacities are not innate but socially and historically constructed. The methodology presented for obtaining information and data collection for this study focused primarily on opened interviews without previous guided instructions, with six women/mothers who experienced this educational experience of early childhood for at least a year, from 2003 to 2008, when the Educriança Programme took place in the city of Guarulhos. The most evident meaning in their statements is that this Programme is another way to live and understand childhood. This Programme revealed itself as a broad experience of education of childhood and have afforded better opportunities for basic care and educational activities at the place where the children lived with their families, since it was based on the concept of family as an educational agent, taking the mother figure as the main reference for childhood education, especially when related to transmitting values, socialization, children habits and accumulated knowledge in their social groups and their own social class